Between Home and the Front : Civil War Letters of the Walters Family - Paone, Thomas J. (Thomas John); Heidelbaugh, Lynn (Book collections on Project MUSE., 2022)
"The personal letters of Americans during the Civil War preserve first-person records of news, people, and emotions that humanize the horrific events of the Civil War and provide unique insights into the conflict's effects on individuals, families, communities, and America. Often, however, only the letters sent home survived, leaving half of the story missing. Between Home and the Front presents previously unpublished letters from Walters family's collection held in the Smithsonian's National Postal Museum, which include the exchange of correspondence between the home front and front line, a perspective not often seen. Between Home and the Front gives us a glimpse into the poignant questions, answers, and sentiments Private David Walters of the 5th Indiana Calvary and his wife Rachel shared in their correspondence. The letters from David give details about some of the lesser-known actions of the western theater of combat, such as Morgan's Raid. The letters by Rachel Walters at home show how she became the hub of communication for the family, often receiving missives from David's brothers, Isaac and John Wesley, both of whom served with Indiana units, and relaying the information to others. From the early letters describing a Civil War soldier's enlistment to his widow's struggle in the aftermath of the war, the letters of the Walters family add incomparable details to the study of the Civil War. Between Home and the Front offers not only a unique first-person account from those that experienced the Civil War but an annotation in meticulous detail to provide valuable historical context for the events, people, and material culture described in the letters"--